Interventions to Prevent Musculoskeletal Disorders and Education on Liquid Waste Management among Weavers on Letti Island: Intervensi Pencegahan Musculosceletal Disorder dan Edukasi Pengelolaan Limbah Cair pada Penenun di Pulau Letti - Syamsuar Manyullei; Vanny Leutualy; Dicky Alamsyah; Ilham Bakri; A Wahyuni; Joanna Cristy Patty; Micrets Agustina; Valensya Yeslin Tomasoa (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Knowledge regarding ergonomic positions and chairs specifically designed to support comfort when working is very much needed by weavers when working. This will prevent the occurrence of Musculoskeletal Disorders (MSDs), explicitly conditions that can affect muscles, bones and joints. The method used in this activity is qualitative observational. This activity was carried out at the Niawarat and Raitawun Weaver Group on Leti Island, Southwest Maluku District. This community service activity began by providing education regarding MSDs and environmental sanitation related to trash and liquid waste from weaving, followed by education on using healthy, ergonomic chairs on non-machine looms. The results of the evaluation of weavers' knowledge were measured using process evaluation, specifically during the process of providing materials and output evaluation, explicitly by asking questions after the activity was completed, and skills in using an ergonomically healthy chair. It is hoped that this activity can be sustainable by the weaving group so that they remain healthy and productive.